Environmental governance in Malaysia : An overview - Mohd Anuar, Haslinda (2014)
The importance of environmental issues was first discussed during the Stockholm Conference on Human Environment in 1972.Later, the United Nations Conference on Sustainable Development 1992 reinforced the needs for effective environmental protection which includes the role of various actors and stakeholders in this environmental issue.The concept of sustainable development was also introduced to give balance between economic development and protection of environment.All environmental issues are captured under environmental governance which contains the management of all man activities including politics, social and economics.The objective of this paper is to focus on the concept of environmental governance and its current status in Malaysia.Some environmental issues are also discusses to yield the effectiveness of environmental governance in Malaysia.